PENGARUH PENGETAHUAN PRODUK, LABEL DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL DENGAN HARGA SEBAGAI MEDIASI: Dibuat oleh Artantri Nugraheni, Sobrotul Imtikhanah dan Fadli Hudaya (Dosen dan Maahasiswa FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Fadli Hudaya; Artantri Nugraheni; Sobrotul Imtikhanah (Neraca, 2021)
This study aimed to analyze the effect of Product Knowledge, Halal Label and Promotion on Purchasing Decisions of Halal Cosmetics Products with Price as a Mediation variable. The object in this study was a student at the Faculty of Economics and Business, University of Muhammadiyah Pekajangan Pekalongan. The sampling technique used was purposive sampling technique with a sample of 100 respondents. Primary data was collected through questionnaires using a Likert scale. The analysis technique in this study used path analysis with the mediation test using the Sobel test. The results of this study indicated that: (1) Product Knowledge had a significant effect on Purchasing Decisions for Halal Cosmetics Products. (2) Halal Label had a significant effect on Purchasing Decisions for Halal Cosmetic Product. (3) Promotion had a significant effect on the Decisions to Purchase Halal Cosmetics Products. (4) Price can be a mediating variable between Product Knowledge, Halal Label and Promotion on Purchasing Decisions of Halal Cosmetics Products. Keywords: Product Knowledge, Halal Label, Promotion, Purchasing Decisions and Price.